POLAR TRANSPORTATION EQUIPMENT - HYDRAULIC CRANES FOR CARGO VEHICLES. - Sherwood, Gerald E.; Beard, William H. (1965)
A hydraulic crane mounted on a 6 by 6 truck-tractor was tested at McMurdo, Antarctica, during the summer season of Deep Freeze 65. The crane had a maximum lifting capacity of 7,600 lbs with a 5-ft boom radius. Its maximum boom radius was 18 ft and its maximum lifting height was 23 ft. It could be rotated 360 degrees and it was easy to operate without special training. The crane was useful in assembling equipment, moving fuel drums, loading and unloading cargo, and camp maintenance. The boom rotation and extension provided good control for accurate and easy placement of material. Similar cranes are commercially available in a variety of sizes for most any size wheeled or tracked cargo vehicle. It was concluded that a hydraulic vehicle crane is a useful support item for polar coastal stations and that its use at outlying stations should be investigated. (Author)